Extracellular vesicles in cancer pros and cons: The importance of the evidence-based medicine. (November 2022) - Cappello, Francesco; Fais, Stefano
Abstract: In this paper we want to introduce a hot topic for clinical and translational research in oncology and all the related medical fields: the "exosomology", i.e., the science that looks at exosomes as nanovesicular tools for theranostics. Exosomes are extracellular vesicles (EVs) of nanometric sizes actively secreted by normal and, above all, tumor cells. Among the EVs, exosomes are surely the most investigated and with the most promising results, mainly for what concerns their potential as representing the future of the so-called "liquid biopsy". Unfortunately, the huge and increasing amount of data coming from preclinical studies was not followed by an adequate number of clinical investigations. However, those clinical studies published to date have provided encouraging but probably unexpected results, including the clinical relevance of the exosome plasmatic levels and the overexpression of well-known biomarkers on the circulating EVs. The clinical relevance of exosomes as a source of new tumor biomarkers (e.g., proteins and miRNA) has been sufficiently supported by clear data. We here want to provide our viewpoint about the existing clinical results based on the literature and our own experience to trigger discussion aimed at undertaking a new direction for future investigation on a role of exosomes in cancer diagnosis and treatment. We believe that a more strategic co-operation between the community of basic scientists and the clinical oncologists should be generated soon, in order to investigate the relevance of the impressive amount of data obtained in human tumor cell lines and animal models. For sure we need a more strategic behavior but also a far-sighted scientific investment in a field where nothing should be considered as granted; a field where we need a mutual collaboration between basic science, clinicians, governments and of course industry.